Desarrollo de un Manual de Proceso para la Elaboración de Cerveza Artesanal en la Empresa Tempel Cervecería - Chisaguano Licta, Ingrid Dayanara (2018)
This research was carried in Quito city at TEMPEL CERVECERIA Company, due to its big growth through the years, obtaining international recognition; it has decided to start a phase of implementation of Good Manufacturing Practice (BPM). This proposal for improvement the "Línea de Cervecería Artesanal" is based on the experience of the processes applied in the production lines for the continuous improvement in the manufacture of its products to create a Manual of Good Manufacturing Practice for elaboration of Craft Beer offering to their customers a better quality, service and food safety, it must comply with current legislation imposed, in Ecuador is an order that all the establishments that make different activities of packed, storage and food distribution for human consumption comply with health surveillance and control standards, based on the dispositions established in the executive decree 544 on January 14, 2015. Around the world, the consumption of contaminated food or water can cause a foodborne disease, a product that is processed in unsuitable conditions could also cause very serious injuries. By means of the compilation of information obtained by the observations, inspections, and external and internal audits more the initial diagnosis applied in the plant created procedures, records and instructions of the Manual, likewise improvements were made such as the proper handling of chemical products used in both cleaning and production, storage of raw materials, supplies and their handling obtaining as a result the Manual of Good Manufacturing Practices (BPM) to elaborate Craft Beer, they will allow to achieve with the demand for quality currently required by the market and by the governmental laws of Ecuador.